2008
DOI: 10.1021/jp8089787
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Properties of Aqueous Cetyltrimethylammonium Bromide with External Additives: Ionic Liquid 1-Hexyl-3-methylimidazolium Bromide versus Cosurfactant n-Hexyltrimethylammonium Bromide

Abstract: Understanding the effect of external additives on the properties of aqueous surfactant solutions is of utmost importance due to widespread applications of surfactant-based systems. Role of ionic liquids (ILs) in this regard may turn out to be crucial as these substances are known to possess unusual properties. To unambiguously understand and establish the role of ILs in modifying properties of aqueous surfactant systems, changes in the physicochemical properties of aqueous cetyltrimethylammonium bromide (CTAB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 89 publications
0
49
0
Order By: Relevance
“…with n = 6 and 8) and anions [Br -] in the solution after dissociation. Pandey's group has reported similar conductivity behavior for cationic, anionic and non-ionic surfactants such as CTAB [51], SDS [25,26] and Tirton X-100 [23,24]. At fixed concentration of SDS, cetyltrimethylammonium bromide (CTAB) and cetyltrimethylammonium chloride (CTAC), Pal (Fig.…”
Section: Electrical Conductivity Measurementsmentioning
confidence: 85%
See 1 more Smart Citation
“…with n = 6 and 8) and anions [Br -] in the solution after dissociation. Pandey's group has reported similar conductivity behavior for cationic, anionic and non-ionic surfactants such as CTAB [51], SDS [25,26] and Tirton X-100 [23,24]. At fixed concentration of SDS, cetyltrimethylammonium bromide (CTAB) and cetyltrimethylammonium chloride (CTAC), Pal (Fig.…”
Section: Electrical Conductivity Measurementsmentioning
confidence: 85%
“…While selecting TTAB as the surfactant, we are studying the influence of the investigated ILs on the alkyl chain of the single chain cationic surfactant by comparing the new results with already published results for CTAB [51]. In this respect, here we investigate the affects of concentration and alkyl chain length of ILs in changing the physicochemical properties of the aqueous TTAB solution.…”
Section: Introductionmentioning
confidence: 99%
“…With the possibility of finetuning the amphiphilicity of ILs by changing the alkyl chain length or polarizability of the cation and anion, one can generate specific self-assembled structures. The self-assembling behaviour of ILs has been a focus of many recent investigations [8][9][10][11][12][13][14][15]. But most of the papers have reported the aggregation behaviour of imidazolium based SAILs with different hydrophobic alkyl chains and anions [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the ionic liquid on the surfactant properties depends on the IL structure and concentration. Behera and Pandey [1,4,8] reported that at low concentration some ILs act similarly to an electrolyte decreasing the surfactant cmc whereas at high concentration they behave as a cosolvent increasing this parameter. In the case of the cationic surfactant hexadecyltrimethylammonium bromide (CTAB) the effect of ILs on the surfactant cmc confirms the trend above described [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Behera and Pandey [1,4,8] reported that at low concentration some ILs act similarly to an electrolyte decreasing the surfactant cmc whereas at high concentration they behave as a cosolvent increasing this parameter. In the case of the cationic surfactant hexadecyltrimethylammonium bromide (CTAB) the effect of ILs on the surfactant cmc confirms the trend above described [8][9][10][11][12][13]. However, when IL posses surface activity as reported for long alkyl chain ionic liquids [14][15][16][17][18][19][20][21] and some short alkyl chain ILs [22,23] the ionic liquid / surfactant mixture behaves as a typical binary surfactant system [24][25][26].…”
Section: Introductionmentioning
confidence: 99%